2009
DOI: 10.1016/j.bbr.2008.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous anxiety and stress responses in water maze and Barnes maze spatial memory tasks

Abstract: The effects of abnormally high or low stress on learning are well established. The Barnes maze and Morris water maze are two commonly-used tests of spatial memory, of which the water maze is considered more stressful; however, until now this has not been demonstrated empirically. In the present study, mice matched for performance on commonly-used anxiety tasks were trained on either the Barnes maze or water maze or received no cognitive testing. Water-maze training induced greater increases in plasma corticost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
251
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(261 citation statements)
references
References 30 publications
7
251
1
2
Order By: Relevance
“…It has been suggested that the Barnes maze discriminates spatial learning more clearly than the Morris water maze (Barnes, 1979;Harrison et al, 2009;Patil et al, 2009;Zheng et al, 2009) and is useful when the Morris water maze shows partial impairment. Drd1a…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the Barnes maze discriminates spatial learning more clearly than the Morris water maze (Barnes, 1979;Harrison et al, 2009;Patil et al, 2009;Zheng et al, 2009) and is useful when the Morris water maze shows partial impairment. Drd1a…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the role of D 1 R in spatial learning, we used the Barnes maze because it is less aversive and stressful than the water maze (Barnes, 1979;Harrison et al, 2009), and because previous studies have shown that the same mouse strain can perform differently in different spatial learning tasks Zheng et al, 2009). In the Barnes maze, WT mice quickly learn to escape the open field and reach the black escape box, as shown by the rapid decline in escape latency (Fig.…”
Section: Barnes Mazementioning
confidence: 99%
“…This test is similar to the water maze navigation task in that it examines the ability of the mouse to learn and remember the location of a target zone (spatial learning and memory) (42). However, the Barnes maze has the advantage of avoiding the strong aversive stimulus of swimming that may affect performance (43). The mouse is placed on a circular platform with holes at its outer edge, 1 of which is the correct escape hole.…”
Section: Nox2 Deletion In Bm Cells (Nox2 -/-mentioning
confidence: 99%
“…Here, we used the Y-maze task, which has been validated by our group and others in TgCRND8 mice [24,29,30]. In comparison to the Morris water maze, the Y-maze is less stressful and requires minimal training, thereby minimizing potential confounds of stress hormones and the learning process on outcome measures [31][32][33][34].…”
Section: Spatial Working Memorymentioning
confidence: 99%